2010
DOI: 10.1097/wco.0b013e32833b6019
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of compensatory mechanisms in Parkinson's disease

Abstract: Ascertaining which changes in brain activation in Parkinson's disease are, in fact, compensatory represents a serious challenge. Compensatory mechanisms have been demonstrated from the microscopic, synaptic level to the macroscopic, system level. Augmentation of compensatory mechanisms, in addition to ameliorating the loss of dopaminergic neurons, may represent a joint strategy for overall minimization of disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 49 publications
1
65
1
Order By: Relevance
“…The results of the current post hoc analyses do not provide information on the mechanism/s for the potential additional longterm benefit of 6-month earlier treatment with rotigotine. However, the data are in support of the concept that treatment intervention in the early stages of PD, when there may be a strain on the intrinsic compensatory mechanisms counteracting the dopaminergic deficit and a rapid rate of deterioration, may be beneficial due to supplementation of dopaminergic activity [1,2,6]. Early restoration of the dopaminergic 'tone' may thus help support the compensatory events; if initiation of treatment is delayed, patients may not have the full opportunity to support the compensatory mechanisms and may be less able to stabilize the symptoms of PD.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The results of the current post hoc analyses do not provide information on the mechanism/s for the potential additional longterm benefit of 6-month earlier treatment with rotigotine. However, the data are in support of the concept that treatment intervention in the early stages of PD, when there may be a strain on the intrinsic compensatory mechanisms counteracting the dopaminergic deficit and a rapid rate of deterioration, may be beneficial due to supplementation of dopaminergic activity [1,2,6]. Early restoration of the dopaminergic 'tone' may thus help support the compensatory events; if initiation of treatment is delayed, patients may not have the full opportunity to support the compensatory mechanisms and may be less able to stabilize the symptoms of PD.…”
Section: Discussionmentioning
confidence: 82%
“…Original Research Impact of 6-month earlier versus postponed initiation of rotigotine on long-term outcome: post hoc analysis of patients with early Parkinson's disease with mild symptom severity 1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both groups had no difference in TH‐positive SNpc neurons, ruling out neuroprotective effects. SMR neurofeedback training might enhance compensatory mechanisms, comparable with presymptomatic PD compensation17, 18 or paradoxical movement 19. We found that during L‐DOPA treatment, ON and OFF scores were significantly smaller in SMR neurofeedback‐trained monkeys compared to controls, respectively.…”
Section: Discussionmentioning
confidence: 65%
“…Disruption of this network is associated with pathological states of the brain. On the other hand, changes in the brain wiring may happen also due to compensatory mechanisms [ 146 ]. Similarly to network representations on other levels, we face certain simplifi cation of extremely complex structure of the brain to a set of elements and interactions.…”
Section: Brain-level Networkmentioning
confidence: 99%